Pemikiran Muhammad Iqbal : Pengaruh rekonstruksi pendidikan Islam pada dunia Pendidikan tinjauan filosofis antropologis - M Iqbal Lubis; Munzir Hitami; Alpizar Alpizar (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2022)
According to Iqbal's views on Islamic education, people should have the most freedom to move around and express their creativity in order to develop academically, physically, and intuitively. This paper aims to show how Muhammad Iqbal's ideas on Islamic education were reconstructed using an anthropological philosophical analysis. The research methodology used was a review of the existing literature, and the principal sources were the idea of Muhammad Iqbal's thinking and various works regarding Iqbal's thoughts. The Reconstructions of Religious Thought in Islam by Muhammad Iqbal serves as the primary source for this study. The study's findings demonstrated that reconstructing Muhammad Iqbal's educational philosophy on Islamic education in anthropological philosophy has the impact of revealing that people have "Khudi," also known as the ego, which is the human self made up of spirit, heart, soul, and body. These four “Khudi” are taken into account when putting education into practice. The integration of modern and Islamic education is greatly aided through “Khudi”. This implies that Islamic education must include scientific truths as well as discussions of Islamic science. On the other hand, Islamic science must be discussed in general education. Islamic education will improve and become more developed as a result of the integration of the “Khudi” potential that humans possess.